ANALISIS HUBUNGAN IKLIM KESELAMATAN DENGAN KECELAKAAN KERJA DI PT. X TAHUN 2023 - Tiffania Hapsari Paramitha (2023)
Safety climate can be used to predict the probability of work accidents. Low safety climate scores are associated with increased chances of having a workplace accident. This study aims to determine the relationship between safety climate and other variables such as age, job tenure and education level with work accidents at PT.X. This study is quantitative research with a cross-sectional design on a total sampling of 100 workers at PT.X. Data analysis was carried out univariately and bivariately using chi-square and simple logistic regression test. Data were collected using the NOSACQ-50 questionnaire. Based on the results, 63% of workers have experienced work accidents. The average score on seven safety climate dimensions was in the fairly low category (2.70-2.99). The chi-square test showed a relationship between job tenure (p=0.001) and work accidents. However, there was no association between age (p=0.197) and education level (p=0.276) for work accidents. The simple logistic regression test showed a relationship between the safety climate (p=0.0001) and work accidents. Management needs to prioritize safety and encourage workers to achieve the best safety climate perception by actively carrying out OSH activities such as safety patrol and safety briefing to reduced the risk of work accidents.